2022
DOI: 10.1101/2022.06.22.497216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intratumoral mregDC and CXCL13 T helper niches enable local differentiation of CD8 T cells following PD-1 blockade

Abstract: Here, we leveraged a large neoadjuvant PD-1 blockade trial in patients with hepatocellular carcinoma (HCC) to search for correlates of response to immune checkpoint blockade (ICB) within T cell-rich tumors. We show that ICB response correlated with the clonal expansion of intratumoral CXCL13+ CH25H+ IL-21+ PD-1+ CD4 T helper cells (CXCL13+ Th) and Granzyme K+ PD-1+ effector-like CD8 T cells, whereas terminally exhausted CD39hi TOXhi PD-1hi CD8 T cells dominated in non-responders. Strikingly, most T cell recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 84 publications
(144 reference statements)
1
4
0
Order By: Relevance
“…The involvement of Tfh cells in response to anti-PD-1 mAb in lymph nodes represents an intriguing parallel to some recent observations made at the tumor site ( Cohen et al, 2022 ; Gu-Trantien et al, 2013 ; Magen et al, 2022 , Preprint ; Niogret et al, 2021 ; Sánchez-Alonso et al, 2020 ). Indeed, the presence of intratumor CD4 + T cells expressing Tfh markers (including CXCL13 and PD-1 high ) in multiple types of carcinomas is associated with better cancer outcomes ( Gu-Trantien et al, 2013 ; Niogret et al, 2021 ) and favorable responses to anti-PD-1 therapy ( Magen et al, 2022 , Preprint ). Of note, these cells were found to interact with intratumoral DCs ( Cohen et al, 2022 ; Magen et al, 2022 , Preprint ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The involvement of Tfh cells in response to anti-PD-1 mAb in lymph nodes represents an intriguing parallel to some recent observations made at the tumor site ( Cohen et al, 2022 ; Gu-Trantien et al, 2013 ; Magen et al, 2022 , Preprint ; Niogret et al, 2021 ; Sánchez-Alonso et al, 2020 ). Indeed, the presence of intratumor CD4 + T cells expressing Tfh markers (including CXCL13 and PD-1 high ) in multiple types of carcinomas is associated with better cancer outcomes ( Gu-Trantien et al, 2013 ; Niogret et al, 2021 ) and favorable responses to anti-PD-1 therapy ( Magen et al, 2022 , Preprint ). Of note, these cells were found to interact with intratumoral DCs ( Cohen et al, 2022 ; Magen et al, 2022 , Preprint ).…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the presence of intratumor CD4 + T cells expressing Tfh markers (including CXCL13 and PD-1 high ) in multiple types of carcinomas is associated with better cancer outcomes ( Gu-Trantien et al, 2013 ; Niogret et al, 2021 ) and favorable responses to anti-PD-1 therapy ( Magen et al, 2022 , Preprint ). Of note, these cells were found to interact with intratumoral DCs ( Cohen et al, 2022 ; Magen et al, 2022 , Preprint ). In addition, adoptive transfer of in vitro–generated Tfh-like cells can enhance antitumor activity in mouse models ( Cohen et al, 2022 ; Niogret et al, 2021 ), in particular, through the production of IL-21 ( Niogret et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tfh-like cells in non-lymphoid tissues support humoral and cell-mediated responses by recruiting B cells and supplying IL21 ( 21, 23, 26, 27, 30, 31, 42, 61 ). Indeed, a recent study showed that Tfh-like cells recruit precursor CD8 T cells and DCs using the oxysterol metabolite 7α,25-HC, which may support a niche for differentiation of effector cells in hepatocellular carcinomas ( 62 ). Moreover, our meta-analysis on the TCGA cohort of HGSOC and several cohorts of ICB-treated showed the improved clinical response associated with these lymphoid aggregates formed by Tfh-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…To specify an mregDC signature that is conserved across different non-lymphoid tissues, we performed our own independent analysis of mregDCs by collating publicly available scRNAseq data on human and murine cDCs 3,5,24,27,40,51,57 ( Fig. 1a ).…”
Section: Main Textmentioning
confidence: 99%